2021
DOI: 10.1371/journal.pone.0259264
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on rural livelihoods in Bangladesh: Evidence using panel data

Abstract: Rapid assessments have been emerging on the effects of COVID-19, yet rigorous analyses remain scant. Here, rigorous evidence of the impacts of COVID-19 on several livelihood outcomes are presented, with a particular focus on heterogenous effects of COVID-19. We use a household-level panel dataset consisting of 880 data points collected in rural Bangladesh in 2018 and 2020, and employ difference-in-differences with fixed effects regression techniques. Results suggest that COVID-19 had significant and heterogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Here we present a unique comparative and empirical based study, reflecting on pandemic-related impacts and responses on and by diversified farm operations, governments and nongovernmental entities in three very different contexts, revealing fewer devastating impacts than anticipated in large part because of the breadth and depth of multi-level responses across sites. We are, however, aware that this represents just part of the global picture and that many other farms and communities (see e.g., Barrett et al, 2021;Lioutas and Charatsari, 2021;Lopez-Ridaura et al, 2021), especially in the global south (see e.g., Carreras et al, 2020;Morton, 2020;Gatto and Islam, 2021;Rasul et al, 2021), saw more severe impacts and fared worse, as evidenced by a growing literature (Abiral and Atalan-Helicke, 2020;Jámbor et al, 2020;Meuwissen et al, 2021). Our study is an important contribution for understanding both the vulnerabilities and resilience of different actors within the agri-food system during the global COVID-19 crisis, with clear policy recommendations toward a more inclusive, resilient and sustainable food system for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we present a unique comparative and empirical based study, reflecting on pandemic-related impacts and responses on and by diversified farm operations, governments and nongovernmental entities in three very different contexts, revealing fewer devastating impacts than anticipated in large part because of the breadth and depth of multi-level responses across sites. We are, however, aware that this represents just part of the global picture and that many other farms and communities (see e.g., Barrett et al, 2021;Lioutas and Charatsari, 2021;Lopez-Ridaura et al, 2021), especially in the global south (see e.g., Carreras et al, 2020;Morton, 2020;Gatto and Islam, 2021;Rasul et al, 2021), saw more severe impacts and fared worse, as evidenced by a growing literature (Abiral and Atalan-Helicke, 2020;Jámbor et al, 2020;Meuwissen et al, 2021). Our study is an important contribution for understanding both the vulnerabilities and resilience of different actors within the agri-food system during the global COVID-19 crisis, with clear policy recommendations toward a more inclusive, resilient and sustainable food system for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Disaster events, such as the COVID-19 pandemic (hereafter called "the pandemic"), can radically change agricultural landscapes (Eklund et al, 2016;Epstein et al, 2018;Lopez-Ridaura et al, 2021) and influence the adoption of new farming practices, crop choices and distribution mechanisms (Lin, 2011;Altieri et al, 2015;DiCarlo et al, 2018;Barrett et al, 2021), indeed, disasters can become critical moments of transformation (Folke, 2006;Bacon et al, 2012;Scheffer et al, 2012;Lioutas and Charatsari, 2021). This research builds on the important and burgeoning canon of literature that looks at rural livelihoods (Du et al, 2005;Valdés and Foster, 2010;Carreras et al, 2020;Gatto and Islam, 2021;Rasul et al, 2021), livelihood diversification (Gautam and Andersen, 2016), and smallholder farming (Hazell et al, 2010;Jayne et al, 2010), in the context of shocks. Given the pervasiveness and increasing frequency of human-environmental induced disasters, especially related to climate and health, there is widespread interest in understanding their impacts on agricultural systems broadly, as well as in the capacity of farmers to recover and adapt (Scheffer and Carpenter, 2001;Adger et al, 2005;Bacon et al, 2012;Kremen et al, 2013;Marín et al, 2014;Tendall et al, 2015;Folke et al, 2016;Kremen and Merenlender, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Rahman and Das (2021)found in their study that the COVID-19 pandemic affected about 33 thousand dairy farms in different parts of Bangladesh and drastically collapsed the marketing of milk and milk products resulting in heavy loss of farmers. Gatto and Islam (2021) founda significant relationship in their rapid assessments of the effects of COVID-19 on agricultural production. Popat et al (2020)found that during the COVID-19 pandemic, the daily demand for milk in the market was continuously decreasing.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Particular priority should be given to the households in which someone has fallen sick to COVID-19, as these were often severely affected by issues surrounding agricultural production, whereas households that were affected by travel restrictions, market closures, etc. suffered relatively less-severe impacts [57]. The design of the rescue policy packages should consider the following: (a) Smallholder fishers, whose livelihoods have been most heavily impacted by COVID-19, need food and cash for their survival and continued production.…”
Section: Policy Recommendationsmentioning
confidence: 99%